Literatur Review : Pengaruh Analisis Balanced Scorecard (Bsc) Terhadap Perspektif Kinerja Keuangan Perusahaan - Septa Dinda Alfia, Famia; Ardilla, Alfin; Suhartini, Dwi; Susilowati, Endah (Fakultas Ekonomi Universitas Gresik, 2023)
Balanced Scorecard that in order to obtain good financial performance results, non-financial performance also needs to be considered because financial performance results are based on non-financial performance. Managers who succeed in achieving a high profit level will be considered successful and obtain a good imbalance from the company, measuring good performance by measuring not only how much income can be obtained, but what factors drive an increase or decrease in a company's income. measures company performance on four balanced (balanced) perspectives: financial, customer, internal business processes, and learning and growth processes. The Balanced Scorecard makes it possible to measure what has been invested in the development of human resources, systems and procedures, for future performance improvement. The financial perspective in the balanced scorecard is defined as a tool used to measure an organization's strategy in increasing its profitability, shareholder value, and business growth. The research methods used in problem solving include this research method to obtain data regarding articles that contain the effect of Balanced Scorecard (BSC) analysis on the perspective of corporate financial performance from data scholars, emeralds, scimago journals and related web journals as well as SINTA. The results of this study Analysis. The Balanced Scorecard (BSC) has a positive effect on the company's financial performance perspective